R21/Matrix-M malaria vaccine drives diverse immune responses in pre-exposed adults: insights from a phase IIb controlled human malaria infection trial - Kibwana, Elizabeth; Bundi, Caroline; Kimani, Domtila; Nyamako, Lydia; Keter, Kelvias; Mutiso, Agnes; Ogwang, Rodney; Bellamy, Duncan; Rapi, Katerina; Bajer, Amelia; Provstgaard-Morys, Samuel; Stockdale, Lisa; et al. (Frontiers in Immunology, 2025)
IntroductionThe recently licenced R21/Matrix-M vaccine induces a protective antibody response. In this study, we examined vaccine-induced responses in semi-immune adults in a controlled human malaria infection (CHMI) Phase IIb clinical trial.MethodsPlasma and peripheral blood mononuclear cells from healthy adult volunteers living in coastal Kenya were analysed following vaccination with R21/Matrix-M (n = 19) and CHMI challenge with Plasmodium falciparum (PfSPZ NF54) sporozoites (n = 17). Humoral immunity was evaluated by quantifying antigen specific antibody subtypes and subclasses via ELISA, alongside functional antibody properties including avidity and complement fixation elicited by vaccination and challenge. Antigen-specific memory B cells were characterised using FluoroSpot assays to detect concurrent secretion of multiple antibody isotypes and the frequency and phenotypes of circulating Tfh (cTfh) cells were assessed using multiparametric flow cytometry.ResultsVaccination increased antibody titres across IgA, IgM, and IgG isotypes and IgG1 and IgG3 subclasses but not IgG2 or IgG4 subclasses, targeting different vaccine antigens (full-length R21, NANP, and C-terminus), indicating a broad and heterogeneous response. The responses were maintained over time and, importantly, they demonstrated complement-fixing capabilities. IgG+ and IgA+ antigen-specific memory B cells were boosted but were short-lived for IgA. We observed an increase in total CXCR5+/PD1+ cTfh cells following vaccination and challenge with the predominant Th2/Th17 population.DiscussionWe provide insights into the diverse immune responses induced by R21/Matrix-M vaccination and their potential contribution to protection against malaria. These findings highlight the potential of the R21/Matrix-M vaccination and protection in adults with varying levels of prior malaria exposure.